ESP AS AN APPROACH OF ENGLISH LANGUAGE TEACHING IN ITS - Endang Susilowati (Jurnal Sosial Humaniora, 2025)
According to National Curriculum Preparation Guideline 2004 – 2009, teaching English in ITS is classified into General Studies ( MKU ) and distributed into “ Personality Development – Related subject “ ( MPK – Mata Kuliah Pengembangan Kepribadian ). However, English as subject has been redundantly placed within the ITS curriculum. While under the curriculum preparation guideline the subject falls into the category of Personality – Development related subjects, the course content involves a significant degree of skills that are required by the students during learning process at ITS. The teaching of English at ITS should therefore be designed to meet the demands for personality development, as well as knowledge and skills improvement. In the attempt of meeting these demands, the English teaching staff have agreed to adopt the ESP approach. The popular principle of English for Specific Purposes ( ESP ) is “ Tell me what you need English for and I will tell you the English that you need”. This principle suggests that ESP is an approach to language teaching which is oriented to fulfil learners’needs. So teaching English at the tertiary level for non English Department such as in ITS is still mostly concentrated on the need for the capability of reading relevant text books. The teaching of English is focused on the reading skill specialized in relevant text books which will reinforce the mastery of basic vocabulary and grammar because mastering reading skill is determined mostly by those two elements. However, this shift to gives other study skills such as note taking, group discussion, presentation and academic writing.